Analisis Fenomenologi dan Psikososial Tokoh Utama dalam L’Enfance d’un Chef Karya Sartre - Hariyani Susanti, R.; Aramudin, Aramudin (UIR PRESS, 2023)
This research aims to apply the phenomenological and psychosocial approaches in analyzing the main character in